Sequential assessment of clinical and laboratory parameters in patients with hemorrhagic fever with renal syndrome - Pal, Emil; Korva, Miša; Resman Rus, Katarina; Kejžar, Nataša; Bogovič, Petra; Kurent, Anica; Avšič-Županc, Tatjana; Strle, Franc (PloS one, 2018)
Information on the sequential appearance, duration, and magnitude of clinical and laboratory parameters in hemorrhagic fever with renal syndrome (HFRS) is limited. Analysis of clinical and laboratory parameters obtained serially in 81 patients with HFRS, of whom 15 were infected with Dobrava virus and 66 with Puumala virus. The initial signs/symptoms, appearing on median day 1 of illness, were fever, headache, and myalgia. These were present in 86%, 65%, and 40% of patients and had a median duration of 4, 4, and 5.5 days, respectively. The signs/symptoms were followed by myopia (appearance on day 5), insomnia (day 6), oliguria/anuria (day 6), polyuria (day 9), and sinus bradycardia (day 9.5). These were present in 35%, 30%, 28%, 91%, and 35% of patients; their median duration was 2, 2, 2, 7, and 1 day, respectively. Laboratory abnormalities, including thrombocytopenia, elevated alanine aminotransferase, CRP, procalcitonin, creatinine, diminished glomerular filtration rate, and leukocytosis, were ascertained on admission to hospital or on the following day (day 5 or 6 of illness) and were established in 95%, 87%, 99%, 91%, 94%, 87%, and 55% of patients, and had a median duration of 4, 3, 7, 3, 9, 8, and 2 days, respectively. Comparison of patients infected with Dobrava and Puumala viruses found several differences in the frequency, magnitude, and duration of abnormalities, indicating that Dobrava virus causes the more severe HFRS. In the majority of patients, the classic clinical distinction into febrile, hypotonic, oliguric, polyuric, and convalescent phases of illness is unclear.